Hadits-Hadits Tentang Metode Pendidikan - Wan Enalya; Zahara Tul Husni; Windi Alya Ramadhani; Raju Pratama Marronis; Wismanto Wismanto (Pusat Riset dan Inovasi Nasional, 2024)
Success in transmitting spiritual values ​​(faith and devotion to God Almighty) to students is related to the elements of the education system, especially the way educators convey God's message. The aim of this research is to find out various types of educational methods that can be used according to Hadith. This article will present the hadiths of the Prophet SAW regarding the educational methods implemented by the Prophet. This research uses a qualitative method, a literature approach. Emphasis is placed on qualitative research using a variety of methods, including interpretive and naturalistic approaches to research subjects. This article will present hadiths about the educational methods implemented by the Prophet. The result achieved is that we can find out various kinds of educational methods from the Prophet Muhammad, as well as the story of him teaching educational methods to his friends. Hadiths related to educational activities carried out by the Prophet include: kindness/compassion method, deductive method, parable method, allegorical method, method of providing comparison facilities, method, questioning method, iterative method, demonstration method, experimental method, solution method problems, methodology for giving praise/pleasure.